Une contribution positive à la protection des droits individuels : l'institution de l'ombudsman au Canada - Tremblay, André (Les Cahiers de droit, 1979)
Canada and Quebec have been actively involved in the trend which has resulted in the existence, within the political system, of a new institution : the Ombudsman. While the Government of Canada hesitated for some time before establishing the institution for federal purposes, the Quebec Public Protector has existed for somewhat more than 10 years, and the new institution has been recognized a proper remedy to the weaknesses of the judicial system. This article enumerates some of the weaknesses of judicial review and attempts to demonstrate that citizens are better protected by the Ombudsman because of the simplicity of the available remedies and the efficiency of settlement procedures. The new institution could not be introduced next to the judicial system without creating some problems. This article considers the respective domains which fall within the jurisdiction of the courts and of Ombudsmen, and the conflicts which could arise. Finally, the operation of the courts and of the Ombudsman will be considered, as well as the advantages and deficiencies of both institutions.